THE INFLUENCE OF ONLINE LEARNING ON STUDENT’S LEARNING STYLES AT SMP NEGERI 5 POLEWALI - Luthfiah, Ena; Sakkir, Geminastiti; Sofyan, Ryan Rayhana (JTechLP: Journal of Technology in Language Pedagogy, 2024)
This research aims to analyze the influence of online learning on students' learning styles at SMP Negeri 5 Polewali. The COVID-19 pandemic has brought significant changes in the world of education, especially through the sudden shift from face-to-face learning to online learning. This study aims to analyze the effect of online learning on students' learning styles at SMP Negeri 5 Polewali. This research used qualitative methods with data collection techniques through interviews, observation, and documentation. The research sample involved students of class IX A. The results showed that there are various obstacles in the implementation of online learning, such as limited technology and internet access. However, online learning also affects students' learning styles, which are divided into three main types: visual, auditory, and kinesthetic. Students with visual learning styles find it easier to understand material through pictures and videos, while auditory students are helped more by verbal explanations. Kinesthetic students have difficulty in online learning due to limited physical activity. This research concludes that learning styles affect the effectiveness of online learning, and teachers need to adapt teaching strategies to suit the needs of each learning style to improve student learning outcomes. This research provides implications for the development of more effective and inclusive online learning strategies in the future.